Tren anak berkebutuhan khusus: implikasi bagi sistem kesehatan inklusif dan penguatan deteksi dini berbasis data pendidikan - Grace Esther Caroline Korompis; Meysilia Firjinia Polii; Rocky Wilar; Rima Fien Lolong; Adisti Aldegonda Rumayar (Holistik Jurnal Kesehatan, 2026)
Background: Children with special needs are a group of children with diverse developmental needs who require ongoing, integrated support across health, education, and social aspects. A humanistic and non-stigmatizing approach views not simply as limitations, but as individuals with potential that can be optimized through an inclusive and responsive service system from an early age. Purpose: To analyze the implementation of an inclusive health and early detection system based on education data. Method: A descriptive design with a time series analysis approach was used. The data were sourced from secondary data obtained through the ministry of education's basic education data and the administrative archives of several special needs schools in Manado City, North Sulawesi. The unit of analysis in this study was the number of children with special needs formally registered in the city's special education system. Trend analysis was conducted to describe the pattern of changes in the number of children with special needs over time. Results: The analysis results show an increasing trend in the number of children with special needs in North Sulawesi throughout the observation period, as represented by the linear trend equation y = 21.686x – 42.2, although there was a slight decline in the last year of observation. This upward trend may reflect improvements in the identification and reporting system, increased public awareness of children's developmental needs, and expanded access to more inclusive education and health services. Conclusion: The increasing number of children with special needs in Manado City requires a response through strengthening an inclusive health system integrated with the education sector, particularly in community-based screening and early detection. Utilizing education data as part of a child health surveillance system has the potential to support the planning of more targeted, sustainable, and equitable promotive and preventive interventions, ensuring the fulfillment of every child's right to optimal growth and development. Suggestion: Future research is expected to further integrate cross-sectoral data, particularly in education, health, and social sectors, to obtain a more comprehensive picture of children with special needs. Furthermore, it is necessary to include classifications of special needs types and sociodemographic characteristics of children for more in-depth analysis.   Keywords: Early Detection Based on Education Data; Inclusive Health System; Trends In Children With Special Needs.   Pendahuluan: Anak Berkebutuhan Khusus (ABK) merupakan kelompok anak dengan keragaman kebutuhan perkembangan yang memerlukan dukungan berkelanjutan pada aspek kesehatan, pendidikan, dan sosial secara terpadu. Pendekatan yang humanis dan non-stigmatis memandang ABK bukan sebagai keterbatasan semata, melainkan sebagai individu dengan potensi yang dapat dioptimalkan melalui sistem layanan yang inklusif dan responsif sejak dini. Tujuan: Untuk menganalisis implikasi bagi sistem kesehatan inklusif dan penguatan deteksi dini berbasis data pendidikan. Metode: Desain deskriptif dengan pendekatan time series. Data bersumber dari data sekunder yang diperoleh melalui Data Pokok Pendidikan (Dapodik) Kementerian Pendidikan serta arsip administrasi beberapa Sekolah Luar Biasa (SLB) di Kota Manado, Sulawesi Utara. Unit analisis dalam penelitian ini adalah jumlah ABK yang tercatat secara formal dalam sistem pendidikan khusus di kota ini. Analisis tren dilakukan untuk menggambarkan pola perubahan jumlah ABK dari waktu ke waktu. Hasil: Adanya kecenderungan peningkatan jumlah ABK di Sulawesi Utara sepanjang periode pengamatan, yang direpresentasikan oleh persamaan tren linier y = 21.686x – 42.2, meskipun terdapat penurunan ringan pada tahun terakhir pengamatan. Tren peningkatan ini dapat mencerminkan perbaikan sistem identifikasi dan pelaporan, meningkatnya kesadaran masyarakat terhadap kebutuhan perkembangan anak, serta perluasan akses layanan pendidikan dan kesehatan yang lebih inklusif. Simpulan: Terdapat peningkatan jumlah ABK di Kota Manado perlu direspons melalui penguatan sistem kesehatan inklusif yang terintegrasi dengan sektor pendidikan, khususnya dalam aspek skrining dan deteksi dini berbasis komunitas. Pemanfaatan data pendidikan sebagai bagian dari sistem surveilans kesehatan anak berpotensi mendukung perencanaan intervensi promotif dan preventif yang lebih tepat sasaran, berkelanjutan, dan berkeadilan, guna menjamin pemenuhan hak tumbuh kembang optimal bagi setiap anak. Saran: Penelitian selanjutnya diharapkan lebih mengintegrasikan data lintas sektor, khususnya pendidikan, kesehatan, dan sosial, untuk memperoleh gambaran yang lebih komprehensif mengenai ABK. Selain itu, perlu memasukkan klasifikasi jenis kebutuhan khusus serta karakteristik sosiodemografis anak untuk analisis lebih mendalam.   Kata Kunci: Deteksi Dini Berbasis Data Pendidikan; Sistem Kesehatan Inklusif; Tren Anak Berkebutuhan Khusus.